Parameters of Physical Performance of Qualified Football Players in the Preparatory Period of Training - Doroshenko, Igor; Svatyev, Andrii; Sobol, Eduard; Danylchenko, Sviatoslav; Doroshenko, Eduard (Journal of Learning Theory and Methodology, 2023)
The purpose of the work: to determine the level of physical fitness of qualified football players in the preparatory period of the annual macrocycle based on test indicators for the formation of rational programs for their preparation for competitive activities. Material & methods. Contingent: 25 qualified football players of MFC “Metalurg” (Zaporizhzhya): 15 athletes – application form «A» and 10 athletes – application form “B” of the second stage of the “Champion” group VBET UA 2022-2023 season of Professional Football League of Ukraine. Methods: Analysis and systematization of data from scientific and methodical literature and the electronic resource of global information network «Internet»; pedagogical observations; pedagogical testing: PWC170 (Physical Working Capacity); Harvard Step-Test; pedagogical experiment of controlling orientation; methods of mathematical statistics. Results. During the educational and training meetings, the test indicators had statistically significant differences in the direction of decreasing values of special physical capacity, from retractable microcycle to percussive microcycle (p<0,05): аPWC170 – 1469,33 ± 50,11 and 1377,67 ± 49,11 (kg•m•min-1), rPWC170 – 20,87 ± 0,69 and 20,71 ± 0,71 (kgm•min-1•kg-1), aVO2 max – 4002,23 ± 115,23 and 3857,54 ± 117,34 (ml•min-1), rVO2 max – 61,57 ± 1,51 and 54,37 ± 1,67 (ml•min-1•kg-1), in accordance. Also, during the educational and training meetings, the test indicators had statistically significant differences in the direction of increment values of special physical capacity: from percussive microcycle to submersible microcycle (p<0,05): аPWC170 – 1377,67 ± 49,11 and 1494,34 ± 51,78 (kg•m•min-1), rPWC170 – 20,71 ± 0,71 and 21,37 ± 0,85 (kgm•min-1•kg-1), aVO2 max – 3857,54 ± 117,34 and 3997,09 ± 114,89 (ml•min-1), rVO2 max – 54,37 ± 1,67 and 63,67 ± 1,71 (ml•min-1•kg-1), in accordance. Conclusion. The way to solve this problem is the proposed methodical approach, which allows, on the one hand, to comprehensively approach the solution of the issue of the complex orientation of the training process of qualified football players in the preparatory period of training, on the other hand, it provides for the differentiation of the team composition into typological groups of athletes, which allows to have a targeted influence on indicators of special physical capacity and technical and tactical potential of qualified football players.